A CAVITATION WEAR ON CENTRIFUGAL PUMP IMPELLENTS MADE FROM HASTELLOY C-276 ALLOY - Rodriguez Gonzalez, Isnel; Columbié, Tomás Fernánde-; Cruz, Jorge Luis Reyes-de la; Torres, Ledennis Suárez- (IJRDO - Journal of Mechanical And Civil Engineering, 2021)
This article establishes the incidence of the leached liquor in the wear, by cavitation, of impellers of a centrifugal pump. The impeller blades, manufactured from the Hastelloy C-276 superalloy, were analyzed. Eight samples which were sectioned from the upper end of the blade, less affected, to the tip of the blade, more damaged. Through scanning electron microscopy (SEM), pitting, rupture of the passive layer, crumbling of the structure, as well as intercrystalline corrosion were evidenced on the surface. It was observed, in diffractograms, the presence of chlorine (Cl), chemical element that forms chloride ions, which prevents the formation of stable layers of oxides. As a result of this phenomenon, the hardness increased from 225 HV to 270 HV, after the analyzed impellers were removed from service.